Genotypic Characterization of Enterotoxigenic Escherichia coli Strains Causing Traveler's Diarrhea - Rivera, FP (2013)
A.M.M. attended a 3-month training course through the CRESIB-UPCH collaborative agreement; training was partially funded by Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica (CONCYTEC, FONDECYT) in Peru. This work was partially funded by the Agencia Espanola de Cooperacion Internacional para el Desarrollo (AECID), Spain, Programa de Cooperacion Interuniversitaria e Investigacion Cientifica con Iberoamerica (D/019499/08, D/024648/09, D/030509/10, and A1/035720/11); Departament d'Universitats, Recerca i Societat de la Informacio de la Generalitat de Catalunya, Spain 2009SGR685 (J.R.) and 2009SGR385 (J.G. and E. A.); and National Institutes of Health, Public Health Service award 1K01TW007405 (T.J.O.); J.R. has a fellowship from program I3 of the ISCIII (grant no. CES11/012)